2012
DOI: 10.1016/j.jebo.2011.06.006
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the menstrual cycle and hormonal contraceptives on competitiveness

Abstract: a b s t r a c tWe examine whether competitiveness in women is influenced by biological factors. Female participants in a laboratory experiment solve a simple arithmetics task first under a piece rate and then under a competitive tournament scheme. Participants can then choose which compensation scheme to apply in a third round. We find that the likelihood of selecting into the competitive environment varies strongly and significantly over the menstrual cycle and with the intake of hormonal contraceptives. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
95
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(104 citation statements)
references
References 44 publications
8
95
1
Order By: Relevance
“…Only females taking hormonal contraceptives were included in the analysis because the menstrual cycle is known to affect the cortisol response to stress (Kirschbaum et al 1999) and may also influence competitiveness (Buser 2012 ;Wozniak et al 2014). To avoid confounding influences we therefore decided to include only women using hormonal contraceptives.…”
Section: A Details About the Inclusion Criteriamentioning
confidence: 99%
“…Only females taking hormonal contraceptives were included in the analysis because the menstrual cycle is known to affect the cortisol response to stress (Kirschbaum et al 1999) and may also influence competitiveness (Buser 2012 ;Wozniak et al 2014). To avoid confounding influences we therefore decided to include only women using hormonal contraceptives.…”
Section: A Details About the Inclusion Criteriamentioning
confidence: 99%
“…Some previous studies have found hormonal variation over the menstrual cycle to relate to risk taking (Bröder andHohmann 2003, Chavanne andGallup 1998; see also Buser 2012b and Schipper 2014 for null results), competitiveness (Buser 2012b, Wozniak et al 2014, behavior in social preference games (Buser 2012a), loss aversion (Lazzaro et al 2016), and competitive bidding (Pearson andSchipper 2013, Schipper 2015). Taken together, this literature suggests that hormones associated with fertility and reproduction, like those in OCs, may affect important economic preferences.…”
mentioning
confidence: 97%
“…Taken together, this literature suggests that hormones associated with fertility and reproduction, like those in OCs, may affect important economic preferences. That OCs may impact preferences is further supported by studies comparing the preferences among naturally cycling women, to those of women using OCs (Chavanne and Gallup 1998, Buser 2012b, Chen et al 2013, Pearson and Schipper 2013, Wozniak et al 2014, although these studies do not establish a causal relationship.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…8 There is also evidence that suggests that having same-sex instructors in introductory math or science courses encourages women to major in math or engineering (Carrell et al, 2010), indicating that having a same-sex role model is an environmental factor that could induce women to make choices that they otherwise would not. This paper designed a laboratory experiment to determine whether the gender gap in preference for competition arises from another environmental factor, namely familial 7 'By-nature' studies reported that gender differences in competitive attitudes are influenced by the fluctuation of sex hormones (Buser, 2012;Wozniak et al, 2014;Guéguen, 2012;Dreber and Hoffman, 2007;Archer, 2006;Hoffman and Gneezy, 2010). Prenatal exposure to male sex hormones is also known to predict long-term profitability in financial traders in the City of London (Coates et al, 2009) and performance in sports, such as rankings for sumo-wrestlers (Tamiya et al, 2012).…”
Section: Introductionmentioning
confidence: 99%